Nivel de conocimiento y cumplimiento de los cuidados a pacientes oncologicos con Neutropenia Febril de las Enfermeras del servicio de Emergencia del Instituto Nacional de Enfermedades Neoplasicas ,2020 - Suasnabar-Reyes, Sara-Cecilia (2022)
Febrile neutropenia in cancer patients is an oncologic emergency, due to immunosuppression that leaves the patient vulnerable to bacterial, fungal and viral infections that put his life at risk. Therefore, in addition to timely medical management, adequate nursing care is necessary to prevent or avoid complications. Objective: To determine the relationship between the level of knowledge and compliance with care in oncologic patients with febrile neutropenia in nurses of the emergency department at the National Institute of Neoplastic Diseases. Methodology: Quantitative approach study, descriptive, correlational, cross-sectional, descriptive method. Population: 58 nursing graduates working in the emergency service, 2 instruments developed by the researchers were applied, for the knowledge variable a questionnaire was used as an instrument, for the variable compliance with the care of the patient with febrile neutropenia a checklist was used. Results: 86.2% of the nurses presented a high level of knowledge and 13.8% a medium level of knowledge. Regarding patient care compliance, it was found that 77.6% of the nurses performed regular care and 22.4% performed good care. Regarding the association of the variables, a p= .796 was obtained between the level of knowledge and care compliance and a Spearman's Rho coefficient (-.035), which determines that there is no relationship between the variables. Conclusions: In the present study it was evidenced that there is no relationship between the level of knowledge and care compliance in oncologic patients with febrile neutropenia in the nurses of the Emergency Department at the National Institute of Neoplastic Diseases.